Marie-Grace and the orphans - Buckey, Sarah Masters, 1955- (American girls collection., 2011)
When Marie-Grace discovers a baby outside her father's office and a slave catcher claims the boy, she helps place him at a white orphanage where she becomes a volunteer, as her friendship with Cécile grows and she hears rumors of yellow fever.